Gynecological aspects of sexual dysfunction in the postmenopausal women - E.A. Sandakova; I.G. Zhukovskaya (LCC «Medicine-Inform», 2023)
E.A. Sandakova1, I.G. Zhukovskaya2 1Academician E.A. Vagner Perm State Medical University, Perm, Russian Federation 2 Izhevsk State Medical Academy, Izhevsk, Russian Federation Sexuality is defined as a physical, emotional, psychological, and social welfare state associated with sexual desires. The prevalence of sexual dysfunction among postmenopausal women is estimated to be 68% to 87%. The most significant causes of sexual disorders in this period are physiological changes of female body, psychological problems, lack of special knowledge, and male health status. Sexual function is linked to the complex neurotransmitter-hormone interaction both at the central and peripheral levels. The major cause of sexual dysfunction in postmenopausal women is genitourinary menopausal syndrome. Most commonly, gynecologist becomes a first contact physician dealing with female sexual disorders. Sexual dysfunction diagnosis in postmenopause includes the use of validated questionnaires, the assessment of the type and severity of menopausal disorders, the impact of somatic diseases and psychological issues, as well as a thorough physical examination. As sexual  dysfunction in postmenopausal women is caused by multiple factors and has a complex pathogenesis, it is necessary to set up a multidisciplinary approach to problem solving. According to the biopsychosocial model, gynecologist has a wide range of therapeutic options for dealing with sexual disorders - pharmacotherapy (hormonal and non-hormonal agents), rational psychotherapy, and multimodal treatment methods. Keywords: sexual dysfunction, postmenopause, sexual hormones, estrogens, androgens, genitourinary menopausal syndrome, biopsychosocial model of healthcare. For citation: Sandakova E.A., Zhukovskaya I.G. Gynecological aspects of sexual dysfunction in the postmenopausal women. Russian Journal of Woman and Child Health. 2023;6(1):26-30 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-26-30.